2013
DOI: 10.1021/cn300219n
|View full text |Cite
|
Sign up to set email alerts
|

Ruthenium Red Colorimetric and Birefringent Staining of Amyloid-β Aggregates in Vitro and in Tg2576 Mice

Abstract: Alzheimer's disease (AD) is a devastating neurodegenerative disease most notably characterized by the misfolding of amyloid-β (Aβ) into fibrils and its accumulation into plaques. In this Article, we utilize the affinity of Aβ fibrils to bind metal cations and subsequently imprint their chirality to bound molecules to develop novel imaging compounds for staining Aβ aggregates. Here, we investigate the cationic dye ruthenium red (ammoniated ruthenium oxychloride) that binds calcium-binding proteins, as a labelin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 43 publications
(79 reference statements)
0
5
0
Order By: Relevance
“…The existence of a hydrophobic cleft between Phe 20 and Val 18, that forms as a consequence of the assembly of Aβ monomers to form the fibril, has been previously discussed. Computational, biophysical and photochemical methods have been used to validate this hydrophobic cleft, which is exposed to the aqueous interphase, and can accommodate this hydrophobic extended systems [66,123] . Therefore, it can be extrapolated that hydrophobic aromatic molecules in general will bind (and could be employed as binding elements) to Aβ fibrils.…”
Section: Discussionmentioning
confidence: 99%
“…The existence of a hydrophobic cleft between Phe 20 and Val 18, that forms as a consequence of the assembly of Aβ monomers to form the fibril, has been previously discussed. Computational, biophysical and photochemical methods have been used to validate this hydrophobic cleft, which is exposed to the aqueous interphase, and can accommodate this hydrophobic extended systems [66,123] . Therefore, it can be extrapolated that hydrophobic aromatic molecules in general will bind (and could be employed as binding elements) to Aβ fibrils.…”
Section: Discussionmentioning
confidence: 99%
“…16) as an Aβ labeling agent. 101 Under light microscopy, Aβ plaques in brain sections of Tg2576 mice were dyed red by 93; under cross-polarization, birefringence was observed when 93 bound to Aβ plaques. However, in addition to Aβ plaques, neurons in the dentate cellular layer of the hippocampus and the Purkinje layer of the cerebellum were also stained by 93, which is undesirable for Aβ-specific dyes.…”
Section: Non-radioactive Ruthenium and Rhenium Complexes Binding To Amentioning
confidence: 98%
“…Consequently, one of the approaches for the treatment of this pathology is to inhibit Aβ fibrillogenesis. With this aim, Sun et al prepared chiral penicillamine-capped selenium (L(D)-Pen@Se) NPs that could perform as Aβ inhibitors [69]. They observed that D-Pen@Se NPs were more efficient inhibitors and they improved both understanding and memory impairments.…”
Section: Biomedicinementioning
confidence: 99%
“…A characteristic of Alzheimer's disease (AD) is the misfolding of amyloid-β (Aβ) into fibrils and its accumulation into plaques [69]. Consequently, one of the approaches for the treatment of this pathology is to inhibit Aβ fibrillogenesis.…”
Section: Biomedicinementioning
confidence: 99%